1978
DOI: 10.1002/1097-0142(197811)42:5<2282::aid-cncr2820420528>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The regressing thin malignant melanoma. A distinctive lesion with metastatic potential

Abstract: To validate the supposition that thin malignant melanomas (less than 0.76 mm thick) of ordinarily low risk but with areas of regression may paradoxically metastasize, we observed 121 thin malignant melanomas over a six year period. Of these, 23 displayed readily apparent areas of regression, of which five (21.7%) metastasized. The incidence of metastases in their 98 counterparts without regression was 2.0% (2/98). The difference between the two is statistically significant (p = less than .01). Of the entire gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(87 citation statements)
references
References 12 publications
3
80
1
3
Order By: Relevance
“…The immune system is capable of mediating the spontaneous regression of solid human tumors, most notably, melanoma and renal cell carcinoma (RCC), 1,2 with tumor-specific CD8 C cytotoxic T lymphocytes (CTL) implicated as major antitumor effector cells.…”
Section: Introductionmentioning
confidence: 99%
“…The immune system is capable of mediating the spontaneous regression of solid human tumors, most notably, melanoma and renal cell carcinoma (RCC), 1,2 with tumor-specific CD8 C cytotoxic T lymphocytes (CTL) implicated as major antitumor effector cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been frequently observed that, at the time of clinical detection, the primary cutaneous melanoma may exhibit histological regression, 29 and that in up to 5% patients with metastatic disease, no obvious primary lesion is identified, suggesting that the primary lesion had been completely eradicated by the immune system. 30,31 The role of cytokines in tumor surveillance and vaccineinduced protective antitumor response has been suggested. Murine knockout models showed that animals deficient in the expression of IFN-g, type I or type II IFN receptors, or some of their downstream signal-transduction intermediates have a higher frequency of tumors compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos mostraram que MCFs com regressão representam um grupo com alto risco de metástases (4,7,13,14,26,28) ,enquanto outros não demonstraram relação entre estes fatores (12,19,20,21,27,32) . Também tem sido sugerido que tal influência negativa seria mais relevante entre os MCFs do que entre os melanomas espessos, sendo a regressão relacionada com alguns casos de metástases em melanomas in situ (MIS) (6,12,14) .…”
Section: Tabelaunclassified
“…Nos resultados dos trabalhos relatados também encontramos variações nos critérios fundamentais para o estudo do prognóstico dos pacientes, entre eles: a) definição de "melanoma fino" adotada, que variou de ≤ 0,76mm, segundo Paladugu et al (28) e Gromet et al (13) , até ≤ 1,5mm, de acordo com Massi et al (23) ; b) tempo de acompanhamento, que variou de um ano, conforme relato de Gromet et al (13) , a 10 anos, segundo Slingluff et al (33) ; c) níveis de Clark -alguns autores excluíram os casos de melanomas in situ, como Sondengaard et al (35) e Massi et al (23) . Nossa amostragem incluiu um caso de MIS com metás-tase, achado já descrito por outros autores (10,14,33) .…”
Section: Regressão Como Fator Prognósticounclassified
See 1 more Smart Citation